Exploration of Potential Cyclin-dependent Kinases and their Inhibitors to Combat Abnormal Signalling and Cancer - Pilania, Pradeep; Nandi, Sisir; Meena, Dinesh K.; Sharma, Brij K. (Current Signal Transduction Therapy, 2024)
Regulation of cell proliferation depends on stimulatory and inhibitory factors that act in a coordinated manner in response to external signals. Various agents, including mitogens, growth factors, cytokines, and other external factors, can impact the mitotic cell cycle, resulting in either provoking growth, differentiation, or apoptosis. Many kinases, such as protein kinases, regulate mitotic cell proliferation through normal signalling. One of the major protein kinase family members is cyclin-dependent kinases (CDK), which are responsible for the regulation of cell cycle progression. If the cell cycle-regulatory mechanisms are permanently altered, it can cause abnormal proliferation that leads to neoplasia. This can result in tumour development, where the availability and expression of CDKs become altered, contributing significantly to impaired cell proliferation. Changes like these are often a characteristic of cancer. CDK inhibitors have shown significant clinical benefits in treating various types of tumours in recent years. The output has been achieved by the clinical approvals of particular CDK inhibitors. Researchers have also been studying the proteolysis-targeting chimera (PROTAC) molecule for the last two decades. This molecule uses ubiquitin-mediated proteasome mechanisms to break down specific targets, making it a promising method for targeted protein degradation (TPD). TPD has become a promising therapeutic option for tackling disease-causing proteins that are otherwise challenging to treat using traditional small molecules. This review provides an overview of the state of knowledge and a general understanding of selective or nonselective CDK inhibitors and PROTAC degraders currently under development or clinically approved congeners, focusing on improving cancer therapy.
Keywords: proteolysis-targeting chimera